2021
DOI: 10.7759/cureus.14907
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Comorbidities in Psoriasis Patients: A Cross-Sectional Study

Abstract: Background: Psoriasis is a chronic, inflammatory, and immune-mediated dermatological disease of unknown etiology with predominant involvement of the skin, nails, and joints. This study aimed to assess comorbidities patterns in psoriasis patients. Methods: This is a cross-sectional study conducted at King Abdulaziz Medical City (KAMC) in Jeddah, Saudi Arabia. Data were collected through a retrospective chart review of the electronic medical record system (Bestcare, Ezcaretech, Seoul, Korea) and by ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Another, most recent cross-sectional study by Alajmi et al from Jeddah (western region) reported 33.6% unidentified psoriasis. 27 The majority of patients, however, were diagnosed with plaque psoriasis (57.0%), followed by those with psoriatic arthritis (13.3%). There were only a few cases of nail psoriasis (0.8%), pustular psoriasis (1.6%), and inverse psoriasis (1.6%).…”
Section: Dovepressmentioning
confidence: 96%
See 2 more Smart Citations
“…Another, most recent cross-sectional study by Alajmi et al from Jeddah (western region) reported 33.6% unidentified psoriasis. 27 The majority of patients, however, were diagnosed with plaque psoriasis (57.0%), followed by those with psoriatic arthritis (13.3%). There were only a few cases of nail psoriasis (0.8%), pustular psoriasis (1.6%), and inverse psoriasis (1.6%).…”
Section: Dovepressmentioning
confidence: 96%
“…Alajmi et al 2021 27 Jeddah Out of 128 confirmed psoriasis cases, plaque psoriasiswas diagnosed in 57.0%, followed by those with psoriatic arthritis at 13.3%. There were only a few cases of nail psoriasis (0.8%), pustular psoriasis (1.6%), and inverse psoriasis (1.6%).…”
Section: Riyadhmentioning
confidence: 98%
See 1 more Smart Citation
“…Psoriasis can affect individuals of all age groups. Studies in Nigeria and India indicated that the majority of their samples belonged to the fourth decade [ 11 ]. In this study, the highest age distribution was observed among patients aged between 31 and 60 years old (54.1%).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a treatment resistant course and a smaller drug survival of biologics could be hypothesized, as already described by others ( 8 ). The high rate of comorbidities in erythrodermic PsO is well known ( 9 ). PsA, hypertension and kidney disease were remarkably more prevalent in LC5 compared with other classes.…”
Section: Discussionmentioning
confidence: 99%